The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10549-013-2640-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of 95-gene and 21-gene classifier (Oncotype DX) for prediction of recurrence in ER-positive and node-negative breast cancer patients

Abstract: We recently developed a 95-gene classifier (95(GC)) for the prognostic prediction for ER-positive and node-negative breast cancer patients treated with only adjuvant hormonal therapy. The aim of this study was to validate the efficacy of 95(GC) and compare it with that of 21(GC) (Oncotype DX) as well as to evaluate the combination of 95(GC) and 21(GC). DNA microarray data (gene expression) of ER-positive and node-negative breast cancer patients (n = 459) treated with adjuvant hormone therapy alone as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…The 95GC helps classify patients with ER + /HER2-/N0 breast cancer types into high-and low-risk groups. In addition, intermediate risk breast cancer types [recurrence score (RS), 18-30] classified using 21GC ( 21GC RS were calculated using Recurrence Online) can be further dichotomized using a 95GC into low-and high-risk groups (5). This dichotomization is expected to lead to a significant difference in disease prognosis, suggesting the use of 95GC in predicting the prognosis of intermediate-risk breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The 95GC helps classify patients with ER + /HER2-/N0 breast cancer types into high-and low-risk groups. In addition, intermediate risk breast cancer types [recurrence score (RS), 18-30] classified using 21GC ( 21GC RS were calculated using Recurrence Online) can be further dichotomized using a 95GC into low-and high-risk groups (5). This dichotomization is expected to lead to a significant difference in disease prognosis, suggesting the use of 95GC in predicting the prognosis of intermediate-risk breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in multiple gene expression assays have enabled the classification of ER‐positive breast cancer into favorable and unfavorable prognoses. Representative examples of gene expression assays are Oncotype DX, MammaPrint, and Curebest 95GC, which were developed to detect patient subpopulations that do not require adjuvant chemotherapy. Moreover, Prediction Analysis of Microarray 50 (PAM50) which classifies breast cancer into five intrinsic subtypes (luminal A, luminal B, receptor tyrosine protein kinase ERBB2 [HER2]‐enriched, claudin‐low, and basal‐like) based on their biological and histological characteristics, is widely used, as each identifiable subtype has a distinct prognosis and distinct therapeutic strategy, and clinical markers, including ER, PR, HER2, and Ki‐67 can be used as surrogate markers to classify breast cancer types .…”
mentioning
confidence: 99%
“…Several retrospective studies using archived samples from prospective studies found a difference of DFS between the 3 RS groups in a large population of ER+ patients (n=3382), pN031,3436 or pN+ 3739. Other retrospective studies found similar results in a mostly ER+ population4045 ( Table S2 , in supplementary data). Most studies showed a significant association between Oncotype DX ® and breast cancer outcome: in ER+ pN0 patients without systemic treatment,46 in ER+ pN0 patients treated with ET alone,31,36,40,42,4447 and in patients treated with chemotherapy and ET 34,41,43,46,48.…”
Section: Resultsmentioning
confidence: 70%